Effect of the Time of Day of Instruction on Student Learning - Nasim Muhammad; Gaganpreet Sidhu; Seshasai Srinivasan (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2020)
In this work, we analyse the effect of the time of the day of instruction on student learning on a programming course taught to first-year undergraduate engineering students. A total of 174 students were split into three different groups, each with a different class time. All were taught the same material and by the same instructor. It was found that students in the morning and early afternoon groups performed better than those in the late afternoon group. In all three groups, there was evidence of long-term retention of concepts, which is attributed to the intervention-based active learning environment using the principles of constructivism. Specifically, the techniques of reinforcement and feedback help with long term retention and avoidance of learning wrong concepts, aided by immediate corrective feedback.